ANAEROBIC SPIRAL SHAPED RODS ANAEROBIOSPIRILLUM SUCCINICIPRODUCENS - Fasih, Naima; Ali Abullah Hawan; Sultan Ahmad Alkahtani; Fatima Ali Alqahtani; Faris Saif Almasoud (Journal of Ayub Medical College Abbottabad, 2022)
It is a case of bacteremia with anaerobic, spiral-shaped gram-negative rods, Anaerobiospirillum succiniciproducens in a patient with chronic liver disease. This infection had led to fatal outcomes in the patient. Prompt and precise microbiological diagnosis may lead to proper treatment and the auspicious outcome of these infections.